Association between serum and red blood cell folate concentrations and urinary phthalate metabolite concentrations in US adults: evidence from a large population-based study - Huang, Xiaojing; Zhang, Huan; Luo, Yaoyu; Yang, Chenhui; Huang, Jue; Zhou, Ting; Qi, Junfeng; Li, Junlin; Zhu, Shuzhen; Zhang, Yaqin; Zhang, Ling; Sun, Xiaojie (Frontiers in Nutrition, 2025)
BackgroundStudies have suggested that folate may mitigate the impact of exposure to environmental chemicals. We aimed to explore the relationship between blood folate biomarker concentrations and urine phthalate metabolites.MethodsBased on data from the National Health and Nutrition Examination Survey spanning 2005 to 2016, 8,218 participants with measurements of folate biomarkers in blood and phthalates exposure in urine were included. Survey generalized linear regression models and restricted cubic spline and generalized additive models were used to assess the associations between blood folate biomarker and urine phthalate metabolites.ResultsAfter adjusting for covariates, each unit increase in the natural logarithm-transformed serum folate concentration was associated with significant reductions of 7.41% in MEHP and 7.10% in MEHHP. After further adjustment for HEI-2020, these inverse associations strengthened to 8.11% (95% CI: −13.18, −2.76%) for MEHP and 8.07% (95% CI: −14.20, −1.52%) for MEHHP. Quartile analysis revealed that participants in the highest serum folate quartile exhibited significantly lower levels of MEHP, MEOHP, MECPP, and MEHHP compared to those in the lowest quartile (all p for trend <0.01). Furthermore, restricted cubic spline analyses and generalized additive models demonstrated significant inverse linear relationships between serum folate concentrations and MEHP, MEOHP, and MEHHP levels. No significant associations were observed between red blood cell folate concentrations and phthalate metabolites.ConclusionThese findings indicate that folate is associated with reduced concentrations of phthalate metabolites in urine, which may hold significant relevance for the utilization of folate as a strategy to reduce the accumulation of phthalate burden.